STRATEGI PEMBERDAYAAN KORBAN PENYALAHGUNAAN NARKOBA DALAM MENUMBUHKAN KEMANDIRIAN DI WISMA ATARAXIS KABUPATEN LAMPUNG SELATAN - Rohman, Abdul; Achlami HS., MA.; Saifuddin, M. (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2022)
Victims of drug abuse face barriers to interaction because of the negative stigma in society, followed by a lack of optimism, a lack of ability to solve problems, a lack of self-confidence, and then drug abusers have negative self-concepts, tending to view themselves as pessimistic about competence. (1) What is the strategy for empowering victims of drug abuse in fostering independence at Wisma Ataraxis, South Lampung Regency? (2) How are efforts to empower drug abuse victims fostering independence at Wisma Ataraxis in South Lampung Regency? (3) How does Wisma Ataraxis, South Lampung Regency, contribute to empowering victims of drug abuse and fostering independence? Field research with a qualitative descriptive approach is used in this study. Field research with a qualitative descriptive approach is used in this study. Data derived from primary and secondary sources, with data collection techniques such as interview, observation, and documentation, as well as data analysis techniques such as data collection, data reduction, data presentation, and conclusions. According to the findings of this study, the empowerment process produces satisfactory results. Victims of drug abuse who are directly involved in the empowerment process benefit more. They believe the skills they have gained will be useful to them. It is also possible to reduce unemployment and increase economic income with this skill training.